The internal influencing factors on management innovation of SMEs in Fujian Province, China: A conceptual study - Qingying Lin; Debbra Toria Nipo; Ang, Hong Loong (Macrothink Institute, 2025)
Small and medium-sized enterprises (SMEs) play a significant role in the economy of China. In the rapidly developing digital economy, opportunities and challenges coexist. SMEs should invest in appropriate resources to enhance their management innovation capabilities in the digital transformation process, and to improve market competitiveness in this globalized arena of today. There are many factors that influence management innovation. Based on the innovation diffusion theory, this study observed the process model of management innovation to build a conceptual framework for the internal influencing factors of management innovation. It should be emphasized that this study currently lacks empirical verification, more research is necessary to test the effect of internal factors on management innovation. This study establishes a conceptual framework that includes senior management support, employee training and successful adoption of technologies as internal influencing factors for management innovation in SMEs, while also focusing on the mediating role of knowledge sharing. This provides a foundation for subsequent empirical research.